Prevalence of nonsyndromic hypodontia in a south-east Transylvanian region. - Suciu Ilinca Elena; Zalana Alexandru; Hack Marius; Păcurar Mariana ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2021)
Introduction. Clinicians claim that the prevalence of hypodontia has skyrocketed in recent years. However, there is no clear evidence whether it is really a change in dentition in Homo Sapiens or a purely hypothetical observation, due to the advanced modern technology used in the diagnosis of dento-maxillary anomalies.